CLINICAL/TRANSLATIONAL - Pediatric Endocrinology: Turner Syndrome, Growth, Pituitary, Congenital Adrenal Hyperplasia &Amp; Adre 2011
DOI: 10.1210/endo-meetings.2011.part3.p14.p2-725
|View full text |Cite
|
Sign up to set email alerts
|

Hypopituitarism in Pediatric Survivors of Inflicted Traumatic Brain Injury

Abstract: Endocrine dysfunction is common after accidental traumatic brain injury (TBI). Prevalence of endocrine dysfunction after inflicted traumatic brain injury (iTBI) is not known. The aim of this study was to examine endocrinopathy in children after moderate-to-severe iTBI. Children with previous iTBI (n = 14) were evaluated for growth/endocrine dysfunction, including anthropometric measurements and hormonal evaluation (nocturnal growth hormone [GH], thyrotropin surge, morning and low-dose adrenocorticotropin stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In several studies with larger numbers, dysfunction of at least one pituitary axis is reported in a large number of patients (50 to 83%) [11,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…In several studies with larger numbers, dysfunction of at least one pituitary axis is reported in a large number of patients (50 to 83%) [11,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…There is no definite recommendation that routine endocrine evaluation should be carried out following TBI. 13,14 Auble et al recommended that any child with a history of TBI be followed closely for growth velocity and pubertal changes. If growth velocity is slow, prolactin level and a full endocrine evaluation should be undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing severity of traumatic brain injury in early childhood is associated with a progressive reduction in long-term serum thyroid-stimulating hormone concentrations Structural traumatic brain injury (TBI) can result in late-occurring health sequelae, consisting mainly of neuroendocrine dysfunctions. 1,2 Studies have suggested that hypopituitarism is relatively common following TBI in childhood, but recent evidence suggests that the incidence appears to be frequently overestimated. 3 We recently showed that permanent hypopituitarism is rare after both inflicted and accidental structural TBI in early childhood.…”
mentioning
confidence: 99%
“…4 A recent small pilot study reported a subtle reduction in overnight thyroid-stimulating hormone (TSH) surge in children following moderate-to-severe inflicted TBI. 1 Thus, it is unclear whether injury severity can be responsible for more subtle long-term effects on thyroid function in the absence of hypopituitarism. Therefore, we assessed whether severity of TBI was associated with changes in circulating thyroid hormone concentrations in childhood in a cross-sectional study.…”
mentioning
confidence: 99%
See 1 more Smart Citation